HUBUNGAN PENGETAHUAN KEPALA KELUARGA DENGAN PERILAKU HIDUP BERSIH DAN SEHAT DI DESA PATOAMEME - Firmawati Firmawati (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Clean and health life is habit is a reflection of the head of family who always looks after the healthy condition in home. It is done by his awareness and can cause the members of a family take active participation in healthy activities. When we do not get used to live healthy, the will be many deaseas cause by the people in society. The design in this study in descriptive correlation. The population is 969 head of family with the sample 87 respondents. The analysis used is chi square test. The result showsthat there is a relation of background knowledge of head of the family with clean and healthy life habit in p<0,005. It is suggested to the nurses to be consistenly active in giving sosialitation of the importance of clean and healthy life habit.